2020
DOI: 10.1038/s41598-020-73134-9
|View full text |Cite
|
Sign up to set email alerts
|

The allosteric activation mechanism of a phospholipase A2-like toxin from Bothrops jararacussu venom: a dynamic description

Abstract: The activation process of phospholipase A2-like (PLA2-like) toxins is a key step in their molecular mechanism, which involves oligomeric changes leading to the exposure of specific sites. Few studies have focused on the characterization of allosteric activators and the features that distinguish them from inhibitors. Herein, a comprehensive study with the BthTX-I toxin from Bothrops jararacussu venom bound or unbound to α-tocopherol (αT) was carried out. The oligomerization state of BthTX-I bound or unbound to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 68 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…Dimer–monomer transitions regulate the activity of several membrane-bound phospholipases, including PLA 1 and phospholipase A 2 (PLA 2 ). Previously, we showed that PlaF becomes active due to a dimer-to-monomer transition followed by tilting of the monomer in the membrane, resulting in t-PlaF A being the active configuration of PlaF . Here, we addressed the questions of how membrane-bound substrates reach the active site of PlaF A and how the characteristics of the active site tunnels determine the activity, specificity, and regioselectivity of PlaF for medium-chain substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Dimer–monomer transitions regulate the activity of several membrane-bound phospholipases, including PLA 1 and phospholipase A 2 (PLA 2 ). Previously, we showed that PlaF becomes active due to a dimer-to-monomer transition followed by tilting of the monomer in the membrane, resulting in t-PlaF A being the active configuration of PlaF . Here, we addressed the questions of how membrane-bound substrates reach the active site of PlaF A and how the characteristics of the active site tunnels determine the activity, specificity, and regioselectivity of PlaF for medium-chain substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The Role of the N-Terminal Region for Membrane Binding and Enzymatic Activity vvPLA2s contain an α-helical N-terminal region believed to be implicated in critical functions, such as membrane binding, and vital structural areas, such as the substratebinding hydrophobic channel. X-ray structures of PLA2s from the Indian cobra (Naja naja) [47] and the European bee (Apis mellifera) [48] venoms and from human [49] and pig (sus Monomeric and dimeric vvPLA2s are the most common quaternary structures found via X-ray crystallography [19,[34][35][36], and they are supposed to be the most common in solution too.…”
Section: The Vvpla2 Protein-membrane Interfacementioning
confidence: 99%
“…Monomeric and dimeric vvPLA2s are the most common quaternary structures found via X-ray crystallography [ 19 , 34 , 35 , 36 ], and they are supposed to be the most common in solution too.…”
Section: Introductionmentioning
confidence: 99%
“…Dimer-monomer transitions regulate the activity of several membrane-bound phospholipases, including PLA 1 , and PLA 2 [45][46][47][48][49][50][51][52]. Previously, we showed that PlaF becomes active due to a dimer-to-monomer transition followed by tilting of the monomer in the membrane, resulting in t-PlaF A being the active configuration of PlaF [19].…”
Section: Discussionmentioning
confidence: 99%